Penggunaan Metode Heart Dan JSA Sebagai Upaya Pengurangan Human Error Pada Kecelakaan Kerja Di Departemen Produksi - Rohmawan, Faris; Restuputri, Dian Palupi (Department Industrial Engineering, University of Muhammadiyah Malang, 2016)
Occupational health and safety is very important point for a company. CV. XYZ is a company that produces paving and have problem about the occupational accident. There are 4 production procceses that can be couse occupational accidents, which is taking raw materials procces, stirring batter, forming and drying. This case must be analyzed using HEART and JSA method as evaluating effort for occupational accident. The results of HEART method analysing imply that HEP value 0,8632is the most dangerous occupational, that is forpicking gravel from cement mixer machine. After known the value of HEP afterward analyzed using JSA method. The goal is as improvement to occupational accident in the production process in order can be reduced. The result of JSA method analysing are improvement suggestion such us levying mask, hat, design of additional components for machine, additional equipment for pallet and hand pallet, and assigning standart operational procedure.